Oncology healthcare professionals’ awareness and understanding of compassion fatigue and its manifestation in public healthcare facilities, KwaZulu-Natal, South Africa - Phindile Mlaba; Themba Ginindza; Khumbulani Hlongwana (International Journal of Africa Nursing Sciences)
Background: Oncology healthcare professionals (OHPs) are continuously exposed to the pain, suffering and demise of patients in their care, which render them vulnerable to compassion fatigue (CF) and other related conditions. CF is described as ‘the cost of caring’ and is an inevitable occurrence in the healthcare profession. Aim: This study explored the OHPs’ awareness and understanding of CF, including its manifestation in public healthcare facilities. Setting: This research study was conducted in three public healthcare facilities that offer full oncology services in KwaZulu-Natal, South Africa. Methods: This qualitative study was rooted in the exploratory descriptive design which was ideal for deepening our understanding of OHPs’ awareness of CF and its manifestations as experienced by the OHPs. In-depth interviews were conducted among 31 OHPs. Results: Three main themes and seven sub-themes emerged from the data analysis. The main themes were (a) OHPs’ awareness, understanding and manifestation of CF, (b) CF mitigation activities, and (c) The pros and cons of a high-pressure work environment. The themes were centred round the OHPs’ understanding of CF and their workplace experiences that contributed to CF. Conclusion: OHP’s conceptual understanding of CF was superficial, hence educational interventions are required to improve their awareness. OHPs continue to face many workplace challenges that contribute to CF. The findings of this study provide evidence of the need for interventions that are dedicated to the management of CF.